Enhancing Geography Education Students' Competence in Sustainable Development Goals (SDGS): A Lesson Study Approach through LOC-R Learning - Hernita Pasongli; Enok Maryani; Eva Marthinu; Rohana Sufia; Lely A. Nasution (STAI Hubbulwathan Duri, 2025)
Preparing prospective teachers with a solid understanding of the Sustainable Development Goals (SDGs) and strong geographic literacy is essential for promoting sustainable development. This study explores how reflective practice, embedded in the Lesson Study (LS) model, can enhance geography education students’ comprehension of SDGs. Using a qualitative approach, the research was conducted through two LS cycles, each comprising the standard stages: Plan, Do, and See. Data were collected via observation sheets and classroom video recordings to assess student engagement and instructional effectiveness. In the first cycle, several challenges emerged, including poor time management, insufficient geographic literacy, discomfort from observer presence, and difficulty linking global case studies to SDG concepts. The second cycle introduced targeted improvements: the use of visual maps, enriched SDG-related content, and integration of digital technologies. These adaptations significantly enhanced student engagement and understanding. Findings demonstrate that the LOC-R (Local Context–Reflective) learning model, when implemented through LS, effectively helps students relate geographic knowledge to real-world sustainability challenges. Reflective collaboration among educators also contributed to improved instructional strategies. The LS-based LOC-R model shows strong potential in advancing both geographic literacy and critical thinking in the context of education for sustainable development. This approach equips future educators to analyze global issues and devise informed, sustainable solutions.